'Now we can drink, too': Changing drinking practices among Polish-Australian women - Wolska, B.; Saggers, Sherry; Hunt, L. (The Australian Sociological Association, 2004)
This paper examines the effects of migration on the drinking patterns of a group of Polish-Australian women. Contrary to other Australian research on migrant women's drinking practices, this small, qualitative study indicates that many Polish women quickly adopted Australian drinking patterns. However, on special occasions some also took on the so called 'Polish drinking' pattern of consuming mostly spirits, frequently undiluted, to intoxication, characteristic of male drinking in their homeland. In contrast, drinking patterns of young, Polish-Australian women in tertiary education and those who completed their education in Australia, were very similar to those of Australian- born young women. This study suggests that there is a need for further research on drinking patterns among migrant women, drinking practices in the home country and the age of migration.